IKLAN POLITIK BALIHO DAN TAYANGAN IKLAN POLITIK RIAU TELEVISI FIRDAUS-AYAT TERHADAP PEMBERIAN SUARA PEMILIH PEMULA PADA PILKADA PEKANBARU 2017 - Aang Chaarnaillan; Muhammad Firdaus; Belli Nasution (Universitas Riau, 2018)
Local leader election is a political recruitment, that is the selection of people to nominate themselves as regional head either governor or deputy governor, vice regent or deputy regent and vice mayor or deputy mayor. The background of this issue that aimed at finding out how big influence of political advertising billboards and the impression of political advertising to young voters at Taruna Satria Vocational High school Pekanbaru in local leader election Pekanbaru 2017.In This research, the researcher used quantitative research, with correlation analysis and multiple linear regression. The variables in this study are (X1), political advertising billboards, (X2) political ad imperssions, and young voters (Y). The population of this research was all of the teenth grade students. The total number was 200 students , by taking samples of 90 students and the writer used random sampling technique. The method of data collection was done by distributing questionnaires which was filled by students of Taruna Satria Vocational High School Pekanbaru. To analyze the data, the writer used correlation product moment (PPM) by using software SPSS 16.After analyzing the data, the writer found that partially political advertising billboard not affect to young voters. While the impressions of political advertising had a positive effect on young voters. Simultaneosly political advertising billboards and the impression of political advertising positively afftects to young voters at Taruna Satria Vocational High School Pekanbaru with percentage of 54%, meanwhile the remaining 46% was influenced by other factors.